1997
DOI: 10.1172/jci119515
|View full text |Cite
|
Sign up to set email alerts
|

Rho proteins play a critical role in cell migration during the early phase of mucosal restitution.

Abstract: In the intestine, several growth factors stimulate migration of epithelial cells, contributing to the maintenance of tissue integrity. The Ras-like GTPase Rho regulates a signal transduction pathway linking growth factor receptors to the formation of actin stress fibers and focal adhesions, presumed to be important for motility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
120
1
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(130 citation statements)
references
References 50 publications
(38 reference statements)
8
120
1
1
Order By: Relevance
“…Our results also suggest that LPA-enhanced migration is mediated via PTXsensitive G i and is dependent on actin cytoskeletal integrity. Previous work demonstrated that functional RhoA was necessary for EGF-stimulated migration in IEC (47). Because these upstream elements are all shown here to regulate Pyk2 tyrosine phosphorylation in IEC-18 cells, the findings are compatible with a potential role for Pyk2 in cell migration.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our results also suggest that LPA-enhanced migration is mediated via PTXsensitive G i and is dependent on actin cytoskeletal integrity. Previous work demonstrated that functional RhoA was necessary for EGF-stimulated migration in IEC (47). Because these upstream elements are all shown here to regulate Pyk2 tyrosine phosphorylation in IEC-18 cells, the findings are compatible with a potential role for Pyk2 in cell migration.…”
Section: Discussionsupporting
confidence: 87%
“…Rho proteins were shown to be critical for cell migration after experimental wounding in both normal (47) and polyamine-deficient IEC-6 cells (41). However, the mechanisms responsible for effecting this response are incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results might, therefore, indicate that RhoA is not required for cell motility [see also Banyard et al, 2000]. However, other reports indicate that activation of Rho is necessary for the motile behavior of cells [Stasia et al, 1991;Takaishi et al, 1994;Ridley et al, 1995;Santos et al, 1997;Nobes and Hall, 1999]. This discrepancy may reflect cell type specificity [Hall, 1998] and differences in experimental conditions.…”
Section: Discussionmentioning
confidence: 58%
“…Activation of RhoA leads to the subsequent activation of Rho kinase, leading to the formation of stress fibers that contract to pull the cell along the extracellular matrix (28). Although a role for RhoA in enterocyte migration has been postulated, its precise role in mediating enterocyte movement has not been definitively established, and the effects of endotoxin on RhoA activity in enterocytes remain unknown (29). Moreover, the ability of enterocytes to migrate during conditions of high endotoxin exposure, as would be expected during the systemic endotoxemia of NEC, remains unknown.…”
mentioning
confidence: 99%